Eight decades of maize streak virus research - Bosque-Pérez, Nilsa A (Virus research, 2000)
Maize streak virus (MSV) (genus Mastrevirus; family Geminiviridae) causes what is considered the most important and widespread disease of maize in sub-Saharan Africa. Maize streak was named by Storey in 1925. Since his classical work on the virus and its leafhopper vectors of the genus Cicadulina China, MSV has been the subject of intensive research. Aspects concerning the geographical distribution, virus diversity, molecular characterization, vector–virus relationships and resistance breeding are reviewed. Special emphasis is placed on recent studies of MSV ecology and epidemiology in West Africa.